The influence of generalized and arbitrary institutional inefficiencies on the ownership decision in cross-border acquisitions - Falaster, Christian (2021)
Extant studies have focused on conceptualizing and measuring the general quality of the institutions and their impact on an array of firms’ strategies. We distinguish two dimensions of institutional inefficiencies in a host country – generalized and arbitrary – and theorize from a knowledge perspective their impact on the acquirers’ ownership decisions in cross-border acquisitions (CBAs). Our empirical examination of 5522 CBAs by firms entering emerging economies reveals that, when exposed to a higher level of host-country generalized institutional inefficiencies, the acquirer tends to take a lower ownership in a CBA. When exposed to higher levels of arbitrary institutional inefficiencies, however, the acquirer tends to take a higher ownership in a CBA. We further find that these relationships are contingent upon the acquirer’s experience in the host region and technological nature.